2016
DOI: 10.1002/jmri.25543
|View full text |Cite
|
Sign up to set email alerts
|

MR targeted imaging for the expression of tenascin‐C in myocardial infarction in vivo

Abstract: 1 Technical Efficacy: Stage 4 J. MAGN. RESON. IMAGING 2017;45:1668-1674.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Then 100 µL of anti-mouse tenascin-C antibodies was added and stirred for 2 h at 37℃. Finally, the conjugated USPIO was purified with phosphate buffered saline (PBS) and stored in PBS (0.1 M, pH 7.4) at 4℃ (13,14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then 100 µL of anti-mouse tenascin-C antibodies was added and stirred for 2 h at 37℃. Finally, the conjugated USPIO was purified with phosphate buffered saline (PBS) and stored in PBS (0.1 M, pH 7.4) at 4℃ (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…After completing the reaction, the solution was ultrafiltered with a centrifugal filter device (300 Kd, PALL, Port Washington, NY, USA) to remove excess EDC.HCL and Sulfo-NHS. Then 100 mL of anti-mouse tenascin-C antibodies was added and stirred for 2 h at 37 C. Finally, the conjugated USPIO was purified with phosphate buffered saline (PBS) and stored in PBS (0.1 M, pH 7.4) at 4 C (13,14).…”
Section: Synthesis Of Anti-tenascin-c-uspiomentioning
confidence: 99%
“…In addition, TNC inhibits cardiac endothelial cell spreading and enhances migration in response to angiogenic growth factors [ 12 ]. It has been found that TNC was identified as a gene that is abnormally expressed in MI/RI [ 13 , 14 ]. In addition, Jin et al.…”
Section: Introductionmentioning
confidence: 99%